Brand Communication of VATANIKA through “This is Me Vatanika” Program: Sociological and Marketing Analyses - อมาตยกุล, ศรัณย์; มงคลอำนวย, วิรัลพัชร; พลโยราช, ก่อพงษ์ (KKBS Journal of Business Administration and Accountancy, 2019)
This article integrates concepts in mess communication, sign consumption, hedonic product, and brand personality to explain the phenomenon of brand communication of VATANIKA, a world-renowned fashion brand designed and produced by a Thai designer. This paper employs the “This is Me Vatanika” program broadcast in Youtube as a case study. The analysis reveals that these concepts can collectively delineate this phenomenon in a more comprehensive manner. Therefore, this article illustrates an example of drawing from various academic disciplines to harmoniously explicate a single phenomenon. The results from this paper may urge businesses to consider different angles in addition to typical communication and marketing perspectives commonly used to examine consumer’s response to advertising program as this will enable businesses to more effectively succeed in their communication goal.